2018
DOI: 10.1108/ijlss-07-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical and statistical approach of Six Sigma differentiation from other quality systems

Abstract: Purpose The purpose of this paper is to investigate in which management aspects could Six Sigma (SS) methodology help the organization that implements it. Another subject to be examined is the integration of SS and other quality management systems (QMSs) in practice and in a theoretical way. Design/methodology/approach A questionnaire was addressed to 146 Greek companies of all business sectors, with at least one QMS; here was ISO 9001:2008. It included questions concerning the importance of the critical suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Some researchers analyzed also the environmental (green) impact of using quality and operations improvement methods such as lean, SS and lean SS (Chugani et al , 2017); particularly, Garza-Reyes (2015) explored the real necessity of integrating SS to enhance the effectiveness of green lean initiatives. Other mangers and statisticians assumed the possibility to integrate SS with ISO 9001 (Ismyrlis and Moschidis, 2018; Marques et al , 2013). A gap, instead, is still present in the application of fuzzy logic-based SS (Vinodh and Swarnakar, 2015; Yadav et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers analyzed also the environmental (green) impact of using quality and operations improvement methods such as lean, SS and lean SS (Chugani et al , 2017); particularly, Garza-Reyes (2015) explored the real necessity of integrating SS to enhance the effectiveness of green lean initiatives. Other mangers and statisticians assumed the possibility to integrate SS with ISO 9001 (Ismyrlis and Moschidis, 2018; Marques et al , 2013). A gap, instead, is still present in the application of fuzzy logic-based SS (Vinodh and Swarnakar, 2015; Yadav et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work for a similar purpose used scales of different lengths. Surveys using five-point Likert scale were done by Alhuraish et al (2016), Antony and Banuelas (2002), Ismyrlis and Moschidis (2018), Iyede et al (2018), Kalra and Pant (2013), Khalili et al (2017), Kharub (2019), Soti et al (2010) and Stankalla et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…Factors responsible for the successful implementation of both approaches are also common as evident from Table 1. Therefore, practitioners and organisations now use these concepts together as LSS (Ismyrlis and Moschidis, 2018; Manisha et al , 2016; Muraliraj et al , 2018; Singh and Rathi, 2019; Yadav et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been implemented successfully by many large manufacturing companies, such as Motorola, GE, and Honeywell. The study of Ismyrlis and Moschidis ( 2018 ) demonstrated that companies implementing Six Sigma outperform companies that do not incorporate it.…”
Section: Literature Reviewmentioning
confidence: 99%